Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.ajic.2016.04.221
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the impact of the multiplex respiratory virus panel polymerase chain reaction test on the clinical management of suspected respiratory viral infections in adult patients in a hospital setting

Abstract: A retrospective cohort design was used to study the impact of a multiplex respiratory virus panel polymerase chain reaction test in 186 adult patients with suspected influenza-like illness. Decisions regarding continuation of empirical antiviral therapy appear to be impacted by the test. However, the impact on reducing antibiotic use remains unclear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 7 publications
(6 reference statements)
3
15
1
Order By: Relevance
“…In agreement with our data, 2 retrospective analyses from Canada showed that influenza virus positivity led to increased use of antivirals, but test results did not correlate with overall antibiotic use [14,22]. Also, 2 European studies found no association between test results and antibiotic use or overall costs [23,24].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…In agreement with our data, 2 retrospective analyses from Canada showed that influenza virus positivity led to increased use of antivirals, but test results did not correlate with overall antibiotic use [14,22]. Also, 2 European studies found no association between test results and antibiotic use or overall costs [23,24].…”
Section: Discussionsupporting
confidence: 88%
“…The testing panel targeted influenza A and B viruses, respiratory syncytial virus (RSV) A and B, rhinovirus/enterovirus, parainfluenza virus 1-3, adenovirus, human metapneumovirus, and coronavirus OC43 and 229E. The RVP assay developed at the MUHC was validated as having lower limits of detection for all viruses, compared with those for direct fluorescent antibody and culture [14].…”
Section: Rvpmentioning
confidence: 99%
See 1 more Smart Citation
“…In some acute hospital settings, reporting similar results directly to attending physicians has also not been sufficient to change antibiotic prescribing behaviors. [24][25][26] In hospitals, reporting the PCR result to an AMS team along with specific advice from the AMS team about antibiotic cessation is required to impact prescribing behavior. 24 Slow transfer of information, lack of confidence in the results, and other factors within the nursing homes, such as work flow, resident mix, and prescriber preferences for overly cautious antibiotic prescribing, 27 may have affected the outcome of this study.…”
Section: Discussionmentioning
confidence: 99%
“…In an observational study, most patients with respiratory tract infection admitted to the hospital who turned out to have an identified viral pathogen did not have their antibiotics discontinued. 107 On the other hand, the use of a clinical pathway integrating the results of viral microbiology testing with clinical findings and procalcitonin testing could have a role in the safe discontinuation of antibiotics. It is now well established that use of procalcitonin to guide initiation and discontinuation of antibiotic in patients with acute respiratory tract infection leads to less use of antibiotics without worsening the outcomes.…”
Section: Discontinuation Of Antibiotic Therapymentioning
confidence: 99%